PENGARUH KOMITE AUDIT, KUALITAS AUDIT, FINANCIAL DISTRESS DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Ellen Dwi Lestari Liani; Lilis Karlina (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the influence of the audit committee, audit quality, financial distress and capital intensity to tax avoidance. The population in this study is the company property and real estate listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, namely 87 companies. The sample in this study amounted to 12 companies or 60 observation data selected by the methodside purposive. The data used is secondary data obtained from website Indonesia Stock Exchange (IDX) and the analysis used is multiple linear regression analysis with the program Eviews 9. The results of the research show that the audit committee, audit quality andcapital intensity negative and significant effect ontax avoidance, where as financial distress positive and significant effect on tax avoidance. audit committee, audit quality,financial distress andcapital intensity simultaneously significant effect jointly on tax avoidance.